Development and evaluation of a computerised clinical decision support system for switching drugs at the interface between primary and tertiary care - Pruszydlo, Markus Gerhard; Walk-Fritz, Stefanie U.; Hoppe-Tichy, Torsten; Kaltschmidt, Jens; Haefeli, Walter E. (BMC medical informatics and decision making, 2012)
Upon admission to a hospital patients’ medications are frequently switched to alternative drugs compiled in so called hospital drug formularies. This substitution process is a laborious and error-prone task which should be supported by sophisticated electronic tools. We developed a computerised decision support system and evaluated benefit and potential harm associated with its use.